GAMBARAN TINGKAT PENGETAHUAN KADER PKK JUMANTIK TENTANG PEMBERANTASAN DAN PENCEGAHAN DEMAM BERDARAH DENGUE DI RW 04 KELURAHAN RAWA BUAYA JAKARTA BARAT - Abu Bakar (Jurnal Nurse, 2020)
The purpose of this study was to describe the level of knowledge of PKK Jumantik cadres about the eradication and prevention of dengue fever. The type of research used is qualitative using a descriptive research design. This research was conducted in RW 04 Kelurahan Rawa Buaya, West Jakarta, on June 17, 2016. The population in this study were all jumantik cadres in RW 04 Kelurahan Rawa Buaya West Jakata with a total of 31 cadres. In this study a sample of 31 respondents from Jumantik Cadre, taken with a total sampling to represent the population. The data collection used is primary data from respondents through a questionnaire consisting of 16 questions to determine the level of knowledge and secondary data through the puskesmas. The results showed that the majority of jumantik cadres had a moderate level of knowledge of 16 respondents (51.6%), high 14 respondents (45.2%), and low 1 respondent (3.2%). The conclusion is that the highest level of knowledge is 51.6%. Suggestions are expected to make jumantik cadres more active in eradicating and preventing DHF.